2003
DOI: 10.1038/sj.hdy.6800255
|View full text |Cite
|
Sign up to set email alerts
|

Comparative FISH analysis in five species of Eyprepocnemidine grasshoppers

Abstract: The chromosomal localization of ribosomal DNA, and a 180 bp satellite DNA isolated from Spanish Eyprepocnemis plorans specimens, has been analysed in five Eyprepocnemidinae species collected in Russia and Central Asia. Caucasian E. plorans individuals carried each of the two DNAs, but the rDNA was limited to only two chromosomes (S 9 and S 11 ) in sharp contrast to Spanish specimens that show 4-8 rDNA clusters and to Moroccan specimens which carry rDNA in almost all chromosomes. The four remaining species, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…In species showing interpopulation variation in rDNA location, such as Eyprepocnemis plorans (Charpentier, 1825), a spread of rDNA throughout the genome seems to have recently taken place (Cabrero et al, 2003). Guillén et al (2004) worked with humans and chimpanzees and suggested that the elimination of rDNA or gene silencing by methylation is caused by the presence of heterochromatin, which is involved in different mechanisms that inactivate NORs.…”
Section: Discussionmentioning
confidence: 99%
“…In species showing interpopulation variation in rDNA location, such as Eyprepocnemis plorans (Charpentier, 1825), a spread of rDNA throughout the genome seems to have recently taken place (Cabrero et al, 2003). Guillén et al (2004) worked with humans and chimpanzees and suggested that the elimination of rDNA or gene silencing by methylation is caused by the presence of heterochromatin, which is involved in different mechanisms that inactivate NORs.…”
Section: Discussionmentioning
confidence: 99%
“…In Orthoptera and Coleoptera (Cabrero et al 2003a, b, Cabral-de-Mello et al 2011b, intraspecific variation involves a polymorphism in the number of chromosomes that harbour ribosomal clusters. With regard to holocentric chromosomes, the variation recently described in T. infestans populations involves the complete transfer of the rDNA locus from an autosomal position to the X chromosome .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, to dehydrate the material, the slides were placed in a 70, 90, and 100% ethanol series and left them to dry. Double FISH was performed as described in Cabrero et al (2003a).…”
Section: Methodsmentioning
confidence: 99%
“…Cytogenetic analysis: To check that the B-SCAR marker is located in the B chromosome, we performed fluorescent in situ hibridation (FISH), following the procedure described by Cabrero et al (2003a), on embryos obtained from cultures maintained in our laboratory as described in Camacho et al (1991). FISH was performed with two different DNA probes: (1) E. plorans rDNA probe generated by PCR amplification of rDNA internal transcribed spacer (ITS) regions, and (2) B-SCAR DNA amplified by PCR.…”
Section: Methodsmentioning
confidence: 99%